AIE-based super-resolution imaging probes for β-amyloid plaques in mouse brains. (22nd June 2018) - Wang, Ya-Long; Fan, Cheng; Xin, Bo; Zhang, Jian-Ping; Luo, Ting; Chen, Ze-Qiang; Zhou, Qi-Yuan; Yu, Qi; Li, Xiang-Ning; Huang, Zhen-Li; Li, Chong; Zhu, Ming-Qiang; et al.
Abstract : AIE-based super-resolution probes are introduced for the super-resolution imaging of fibrillar amyloids with 30 nm resolution. Abstract : Fluorescence microscopy is an intuitive detection method of β-amyloid (Aβ) fibrillation, which usually occurs in early-stage Alzheimer's disease. With the aid of single-molecular localization of reversibly-activated fluorogens, the limit of optical diffraction in fluorescence microscopy can be overcome and the imaging resolution can be promoted to the sub-100 nm boundary. Aggregation-induced emission (AIE) is the fluorogenic emission behavior in which fluorescence is significantly enhanced due to the restriction of intramolecular motion when the fluorogens aggregate together or bind with specific targets. Reversible binding events of AIE-active fluorogens cause fluorescence switching enabling single-molecular localization and super-resolution imaging. Here, we report a series of super-resolution fluorescent probes with AIE activity, which are used for the detection and super-resolution imaging of fibrillar amyloids. The AIE-active fluorogens show superior in vitro sensitivity to fibrillar amyloids of hen egg white lysozyme (HEWL), which is usually used as a model protein for amyloid studies, with the limit of detection down to 63.71 nM. The fluorescence colocalization imaging indicates the excellent ex vivo targeting capability of Aβ plaques in mouse brain slices, with the colocalization degrees more than 90%. Based on the reversible binding between AIE-fluorogens and Aβ fibrils, the AIE-based super-resolution imaging of in vitro Aβ fibrillation in tubes and ex vivo Aβ plaques in mouse brain slices is accomplished. The detailed structure information reveals that Aβ plaques in the mouse brain are composed of numerous radiant nanofibrils with an optical imaging resolution of about 30 nm.